Evaluation of three immunochromatographic tests for rapid detection of antibodies against SARS-CoV-2 - Gladys Virginia Guedez-López; Marina Alguacil-Guillén; Patricia González-Donapetry; Ivan Bloise; Carolina Tornero-Marin; Juan González-García; Jesus Mingorance; Julio García-Rodríguez; María Dolores Montero-Vega; María Pilar Romero; Silvia García-Bujalance; Emilio Cendejas-Bueno; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

New estimates of greenhouse gas emissions from biomass burning and peat fires using MODIS Collection 6 burned areas - Paolo Prosperi; Mario Bloise; Francesco N. Tubiello; Giulia Conchedda; Simone Rossi; Luigi Boschetti; Mirella Salvatore; Martial Bernoux (Climatic Change, 2020)
The Paris Agreement calls on parties to undertake ambitious efforts to combat climate change by engaging in appropriate policies and measures as put forward through Nationally Determined Contributions (NDCs), to strengthen transparency when reporting their greenhouse gas (GHG) emissions and to increase their mitigation contributions to climate action from 2020. It also calls for regular and transparent monitoring and reporting of the GHG emissions and on the NDCs implementation efforts. Biomass fires significantly affect the GHG atmospheric balance, with fire emissions representing more than 5% of total emissions from agriculture, forestry, and other land use (AFOLU), according to recent estimates produced by the Food and Agriculture Organization (FAO). We update previously published Tier 1 estimates of GHG emissions in FAOSTAT—which had been used in the IPCC AR5 analysis—by using new burned area activity data from the Moderate Resolution Imaging Spectroradiometer (MODIS) known as MCD64A1, Collection 6. The previous FAOSTAT estimates had used as input the Global Fire Emission Database v.4 (GFED4) burned area product, based on older MODIS Collection 5.1 burned area product. In line with differences between the input data used, the new FAOSTAT estimates indicate roughly 30% higher fire emissions globally than previously published. Our analysis also confirms that the FAOSTAT Tier 1 approach produces fire emissions estimates that are comparable to those computed at Tier 3 by GFED, and thus represent a useful complementary tool in support of country GHG reporting.